(untitled) - Tracy, Eileen (New York, NY, 2006)
In addition to fundamental student skills such as timetabling, note-taking, memorising, research, use of the internet, essay-writing and exam technique, The Student's Guide to Exam Success offers ground-breaking advice on developing emotional strength in response to the increasingly heavy demands that are made on students in the modern world. It offers a variety of strategies which will help students to: Find out how to stop procrastinating and worrying about results, and start to enjoy their work; Learn about the dangers of swotting; Develop the necessary confidence to handle reading lists, coursework, presentations and practicals; Learn to deal with tutors, lecturers and examiners.
Keywords: Test-taking skills.,Examinations,Study skills; Study guides